2012
DOI: 10.1161/circulationaha.111.059022
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Versus 12-Month Dual Antiplatelet Therapy After Implantation of Drug-Eluting Stents

Abstract: Background-The optimal duration of dual antiplatelet therapy (DAPT) after implantation of drug-eluting coronary stents remains undetermined. We aimed to test whether 6-month DAPT would be noninferior to 12-month DAPT after implantation of drug-eluting stents. Methods and Results-We randomly assigned 1443 patients undergoing implantation of drug-eluting stents to receive 6-or 12-month DAPT (in a 1:1 ratio). The primary end point was a target vessel failure, defined as the composite of cardiac death, myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
237
3
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 563 publications
(250 citation statements)
references
References 30 publications
5
237
3
5
Order By: Relevance
“…2692 publications were found at initial search and after abstract and manuscript evaluation eleven studies are selected for final analysis ( Figure 1) [3][4][5][6][7][8][9][10][11][12][13]. In selected eleven RCTs, 33, 520 patients were randomized to S-DAPT (N=16, 687) and L-DAPT (n=16,833), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2692 publications were found at initial search and after abstract and manuscript evaluation eleven studies are selected for final analysis ( Figure 1) [3][4][5][6][7][8][9][10][11][12][13]. In selected eleven RCTs, 33, 520 patients were randomized to S-DAPT (N=16, 687) and L-DAPT (n=16,833), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…duration of DAPT have reported conflicting results [3][4][5][6][7][8][9][10][11][12][13]. Previous meta-analyses of RCTs comparing S-DAPT versus L-DAPT have shown inconsistent results [14][15][16][17].…”
mentioning
confidence: 99%
“…In cases, angioplasty had been reported as very useful, but other authors have reported poor long-term results needing the use of stents [1,[10][11][12][13][14][15]. In our patient, the angioplasties performed obtained an excellent immediate result, but really poor intermediate or long-term results.…”
Section: Discussionmentioning
confidence: 44%
“…Drug eluting stents are normal metallic stents coated with a pharmacological agent that interferes with the process of restenosis [10][11][12]. The use of DES is controversial, and there is not much information on the use of these stents especially in the pediatric population [1,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation